Community Participation in The Program for Improving Quality of Unworable Houses in Payakumbuh City - Defi Fradila Sari; Erwin; Afrizal (Institute of Computer Science (IOCS), 2021)
his research begins with the importance of participation in development programs that use limited stimulant funds and from the perspective of development effectiveness. The objectives of this study are: 1) To explain the scope of community participation in the planning and implementation of Improving the Quality of Unfit for Living (PK-RTLH) in Payakumbuh. 2) Analyze possible factors and barriers to participation in the implementation of the Improving the Quality of Unfit for Living (PK-RTLH) program in Payakumbuh. When the research was conducted in January to February 2020. This research was conducted in Payakumbuh City by taking the location in the West Payakumbuh District (Payolansek Village, Padangtangah Balainanduo Village ), Kec.observations of Lampasi Tigo Nagari ( Koto Panjang Dalam Village), North Payakumbuh District (Tigo Koto Diateh Village) and South Payakumbuh District. This study uses a qualitative method. The research informants totaled 22 people consisting of 17 key informants and 5 regular informants. Key informants are recipients of PK-RTLH program assistance, while regular informants consist of 2 facilitators , 1 head of the Housing and Settlement Office , 1 head of the village and 1 person from Niniak Mamak. Based on the results of the research, the forms of community participation in planning to improve the quality of houses for rehabilitation of unfit for habitation are; a) Formation of aid recipient groups ; b) Opening of the beneficiary account number ; c) Utilizing local resources while taking the form of participation in the implementation of the Program for Improving the Quality of Unfit for Living : a) Participation in the form of personnel assistance ; b) Participation in the form of material assistance; c) Participation in the form of skills or expertise. Factors that me Could masyar AKAT to participate include factors intrinsic and e kstrinsik . Intrinsic factors consist of: a) kinship ties; b) the desire to live a decent life . As for extrinsic factors, namely a) group cohesiveness; b) free time. In participation, there are also factors that hinder society from participating, namely: a) Economic factors; b) The influence of modernization so that individualism appears; c) Program information does not reach all elements of society.